The Relationship Between Family Support and Quality of Life in Diabetes Patients At Parongpong Community Health Cen-ter - Sally Kunu; Jeanny Rantung (International Journal Of Health Science, 2025)
Diabetes mellitus constitutes a chronic pathological condition that necessitates continuous therapeutic management throughout a patient’s lifetime and has been widely recognized as a major factor contributing to the deterioration of patients’ physical, psychological, and social well-being, thereby reducing their overall quality of life. Within this context, familial support emerges as a pivotal determinant that not only facilitates patients’ psychosocial adaptation to their illness but also enhances adherence to treatment regimens and coping mechanisms in daily life. Hence, the present study was conducted with the objective of elucidating the relationship between family support and the quality of life among individuals diagnosed with diabetes mellitus who receive treatment at Parongpong Public Health Center. This investigation employed a descriptive correlational research design with a cross-sectional orientation, encompassing a total of 34 respondents who were carefully selected through purposive sampling techniques based on predetermined inclusion criteria. The collected data were subjected to statistical analysis using the Pearson Product Moment correlation test to determine the strength and significance of the association between the studied variables. The findings revealed a statistically significant correlation between family support and quality of life (p = 0.009; r = 0.440), indicating a moderate positive relationship, wherein higher levels of family support corresponded to better perceived quality of life among patients. In light of these findings, it can be inferred that the presence of consistent and meaningful familial involvement contributes substantially to the enhancement of the overall quality of life in diabetes mellitus patients at Parongpong Public Health Center.